Impact of administrative empowerment on organizational learning at Martur Algeria Organization - Lynda, Benguergoura (International journal of economic perspectives, 2024)
This research explores the influence of administrative empowerment on organizational learning processes within MARTUR ALGERIA Organization. The study centers on an independent variable, administrative empowerment, encompassing dimensions such as delegation, teamwork, training, effective communication, and motivation, as well as a dependent variable, organizational learning. Utilizing a carefully designed questionnaire, data was gathered from selected participants and analyzed using the SPSS 26 software. The findings reveal a substantial influence of administrative empowerment on organizational learning at the institution. Based on these insights, the study advocates for a heightened focus on empowering human resources as a pivotal strategy to bolster learning capabilities and achieve organizational excellence.